Oxygen isotopes of bivalves from the Coorong Lagoon, South Australia, from 2016-2018 - Briony Chamberlayne; Jonathan James Tyler; Bronwyn M Gillanders (PANGAEA, 2021)
To assess the fractionation of oxygen isotopes into the bivalve species Arthritica helmsi, live bivalve shells were collected alongside the waters in which they inhabit. Samples were collected at sites along the Coorong Lagoon and Lake Alexandrina in South Australia – the estuarine system at the terminus of Australia extquotesingles Murray River. Whole shell analyses of oxygen and carbon isotopes (n = 135) were measured on samples collected on 6 occasions from November 2016 to May 2018 (https://doi.pangaea.de/10.1594/PANGAEA.932620). Oxygen and hydrogen isotope analyses of waters were measured along with salinity and temperature monthly over the same time period (n = 137; this data set).